INTERCULTURAL EXPERIENCES FROM THE PERSPECTIVE OF NARRATIVE INTERVIEWING: METHODOLOGICAL PITFALLS AND CHALLENGES IN THE EYES OF THE STUDENT AND THE TEACHER - Wąsikiewicz-Firlej, Emilia (Neofilolog, 2020)
This paper attempts to take a critical look at the narrative interview in order to identify the methodological pitfalls and challenges posed by this widely-applied research tool. It analyses the research process in a project involving sixty-four 3rd year students of applied linguistics at a large university in western Poland in the summer term of the academic year 2018/2019. The project included three stages: (1) interviewing a person from another country studying in Poland about their intercultural experiences; (2) transcribing the interviews and (3) presenting the results of their analysis in the form of a written report. On completion of their assignments, the students were asked to share their reflections on all stages of their research in an anonymous survey study. The questionnaire data was juxtaposed with analysis of the student transcripts and reports in order to identify and compare the student and the teacher perspectives on methodological aspects of narrative research. The outcomes of the survey study show that the students, as inexperienced or even first-time researchers, mostly focused on their language proficiency and technical aspects of the interview, while the teacher/researcher pointed primarily to flaws in the formulation of the interview questions and lack of subsequent probing questions, which resulted in superficial responses or even at times deprived the interview of a narrative character. The study also documented the evolution of students as researchers and its results might be applicable for teachers offering courses in academic writing or BA/MA seminars.